PELAYANAN PROFESIONAL PADA PEMBUATAN SURAT IZIN MENGEMUDI KENDARAAN RODA DUA (SIM C) DI SATLANTAS POLRESTA - ", Basri; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Public service is a very strategic role in the State upayah progress in aspired by the people in a country. Therefore, the public service that is effective, simple, clear and definite, open, efficient, timely, responsive, and adaptive. Due to good public services will materialize professional services. Professional services are expected to be done with everything including the service makes the SIM in Pekanbaru Traffic Police. The purpose of this study is to analyze the service in making the two-wheeled vehicle driver's license (SIM C) and knowing the constraints in service in the Police Satlantas Pekanbaru.Descriptive research, which is defined as the process of solving the problem was investigated by exposing or describe the state of the subject and object of research at the present time based on the facts that emerge or that way. In data collection and in-depth interviews the author conducted a search of documents and official records.The results of this study are expected to provide the following benefits: their contributions in order to develop the knowledge, especially in the field of social and political science as well as a reference to improve services, especially in making a driver's license at the Traffic Police Pekanbaru.Results of research conducted at the Traffic Police Pekanbaru through eight indicators considered quite good, but the authors suggest to the Traffic in order to improve services, especially the manufacture of a driver's license two-wheeled vehicles (SIM C) in order to achieve service excellence.Key words: Public Service, manufacture of driving license (SIM C)